2022
DOI: 10.1093/schizbullopen/sgac009
|View full text |Cite
|
Sign up to set email alerts
|

The Latent Structure of Negative Symptoms in the General Population in Adolescence and Emerging Adulthood

Abstract: Negative symptoms predict adverse outcomes within psychotic disorders, in individuals at high-risk for psychosis, and in young people in the community. There is considerable interest in the dimensional structure of negative symptoms in clinical samples, and accumulating evidence suggests a 5-factor structure. Little is known about the underlying structure of negative symptoms in young people despite the importance of this developmental stage for mental health. We used confirmatory factor analysis to test the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…A study that investigated the effect of polygenic liability to schizophrenia GPS on the developmental course of separate dimensions within the negative symptoms construct in schizophrenia found that schizophrenia GPS predicted a more severe course specifically of avolition (Jonas et al, 2019 ). This aligns broadly with suggestive cross-sectional GPS findings in the community (Havers, Cardno, Freeman, & Ronald, 2022 ), and with clinical findings and theory suggesting that avolition may be a central feature of the negative symptoms construct (Foussias & Remington, 2010 ; Strauss et al, 2020 , 2021 ).…”
Section: Discussionsupporting
confidence: 84%
“…A study that investigated the effect of polygenic liability to schizophrenia GPS on the developmental course of separate dimensions within the negative symptoms construct in schizophrenia found that schizophrenia GPS predicted a more severe course specifically of avolition (Jonas et al, 2019 ). This aligns broadly with suggestive cross-sectional GPS findings in the community (Havers, Cardno, Freeman, & Ronald, 2022 ), and with clinical findings and theory suggesting that avolition may be a central feature of the negative symptoms construct (Foussias & Remington, 2010 ; Strauss et al, 2020 , 2021 ).…”
Section: Discussionsupporting
confidence: 84%
“…Although emerging adults have reached physical and sexual maturity, they are still learning and maturing and require protection 14 . It is noteworthy that emerging adults are particularly at‐risk for psychiatric disorders, including bipolar spectrum disorders and schizophrenia 15,16 . In a given year, over 40% of emerging adults meet the criteria for a psychiatric disorder, a higher rate than for any other adult age group in the U.S 17 .…”
Section: Introductionmentioning
confidence: 99%
“… 14 It is noteworthy that emerging adults are particularly at‐risk for psychiatric disorders, including bipolar spectrum disorders and schizophrenia. 15 , 16 In a given year, over 40% of emerging adults meet the criteria for a psychiatric disorder, a higher rate than for any other adult age group in the U.S. 17 Moreover, physical and mental comorbidity is prevalent among emerging adults and psychopathology in emerging adulthood undermines adaptation and reduces the likelihood of successful transitions to adulthood. 18 Furthermore, there is a gap between the need for and the use of mental health services in emerging adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation